George Li performs Prokofiev's Piano sonata no. 4 - Prokofiev, Sergey 1891-1953 (Telmondis - Münchner Philharmoniker, 2017)
A pianist who combines "staggering technical prowess, a sense of command and depth of expression" (The Washington Post), George Li was a silver medalist at the 2015 International Tchaikovsky Competition. Here he performs Prokofiev's Piano Sonata No. 4 as part of the 2016 MPHIL 360°. For the 2016 MPhil 360° festival, Valery Gergiev and the Münchner Philharmoniker put together a musical celebration of impressive proportions! The three-day festival put a special focus on Sergei Prokofiev's piano sonatas performed by honorees of the International Tchaikovsky competition
Keywords: Sonates (Piano); Sonatas (Piano); Webcast; Concert films; Internet videos; Concerts filmés; Vidéos sur Internet